The status of sustainable concrete codes in the United States - Andrew Warren Taylor (Acta Polytechnica CTU Proceedings)
As the focus on embodied carbon within the built environment has grown in the U.S., local jurisdictional codes have increasingly proposed and implemented code language that requires the use of concrete mixtures that have reduced environmental impacts. This paper provides details about the various ways that localized sustainable concrete provisions have been proposed and implemented in the U.S., including limits on cement content and Global Warming Potential (GWP). These laws and code revisions vary in their measurement of low-carbon concrete and their exemptions and incentives. While the current version of the ACI Building Code, ACI 318-19, does allow for the consideration of sustainability in concrete design, specifics about how the relative sustainability of concrete mixtures and systems are to be measured and compared are not included. This paper addresses how the changing landscape of local jurisdictional codes is driving the development of future ACI 318 provisions to play a part in providing more consistency in the application of sustainable design practices in the United States.